The impact of nickel mining on vegetation index in Molawe Sub-district, North Konawe District, Southeast Sulawesi, Indonesia - MOHAMMAD AFDHAL ADIDHARMA; SUPRIATNA SUPRIATNA; NOVERITA DIAN TAKARINA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Adidharma MA, Supriatna, Takarina ND. 2023. The impact of nickel mining on vegetation index in Molawe Sub-district, North Konawe District, Southeast Sulawesi, Indonesia. Biodiversitas 24: 4581-4588. Nickel mining activities in Molawe Sub-district, North Konawe District, Southeast Sulawesi, Indonesia have modified the land cover structure over time due to increased mining exploitation zones. This study intends to assess changes in land cover in the Molawe Sub-district, particularly around mining regions. The NDVI index was applied to Landsat 7 ETM+ satellite imagery data in 2001 to identify land cover conditions before mining activities, then to Landsat 8 OLI imagery data in 2015 and 2020 to identify land cover after mining activities. These data are then used to compute annual changes in the extent of each land cover. The NDVI classification produces four land cover types: non-vegetation, open soil, sparse vegetation, and moderate vegetation. The study shows that non-vegetation and open ground cover types experienced a significant increase in area from 2001 to 2015 and from 2015 to 2020. Meanwhile, sparse vegetation forest cover experienced a reduction in area from 2001 to 2015 and 2015 to 2020. In contrast to sparse vegetation, the moderate vegetation cover is experiencing a minor increase in area. Based on these results, relevant policymakers need to formulate policies to mitigate environmental impacts that may arise in the future.